2012
DOI: 10.1103/physreva.85.053403
|View full text |Cite
|
Sign up to set email alerts
|

Invalidity of the Ehrenfest theorem in the computation of high-order-harmonic generation within the strong-field approximation

Abstract: It is known that the strong-field approximations commonly used in models for computing high-order-harmonic generation invalidate the Ehrenfest theorem. Therefore, the time derivative of the atomic dipole or of the dipole velocity does not correspond to the dipole acceleration. We study the consequences of this invalidation for the quantitative evaluation of high-order-harmonic spectra in hydrogen at different wavelengths and intensities. As a main result, we propose a form for the time derivative of the kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Other attempts to improve the SFA include using different forms of dipole such as dipole acceleration and dipole velocity [88,89,95]. We also mention here other modifications of the SFA by including the effect of field dressing on the bound state [96][97][98].…”
Section: Other Modifications To the Sfamentioning
confidence: 99%
“…Other attempts to improve the SFA include using different forms of dipole such as dipole acceleration and dipole velocity [88,89,95]. We also mention here other modifications of the SFA by including the effect of field dressing on the bound state [96][97][98].…”
Section: Other Modifications To the Sfamentioning
confidence: 99%
“…Although these laser-electromagnetic gauges should provide the same results for a physical observable, for instance, the HHG spectra, previous studies have found that, unfortunately, it is not the case in several systems [29][30][31]. This breaking of the gauge-symmetry occurs when an approximation is carried out to solve the Time-Dependent Schrödinger Equation (TDSE).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This supports the observation that any approximation of the TDSE can break the laserelectromagnetic gauge-symmetry. For instance, in the Strong Field Approximation (SFA) applied to a gas, this laser-electromagnetic gauge-symmetry is broken [34]; producing different HHG spectra, particularly for the emitted intensity yield [30,31]. Nevertheless, the main qualitative features of the high harmonics are reproduced by the LG and VG in the SFA formalism.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The SFA, however, has serious limitations. Apart from the gauge dependence and its influence on the structural interference [28,29,35], different forms of recombination dipole matrix element affect this condition [31,36,37]. The most appropriate form to be used has raised considerable debate in the context of the tomographical reconstruction of molecular orbitals [38][39][40] If the field however is orthogonally polarized, the electron's angle of return is effectively incorporated in the two-center interference condition.…”
Section: Introductionmentioning
confidence: 99%